Genetic analysis of drought resistance in rice by molecular markers: association between secondary traits and field performance - Babu, R. Chandra; Nguyen, Bay D.; Chamarerk, Varapong; Shanmugasundaram, P.; Chezhian, P.; Jeyaprakash, P.; Ganesh, S.K.; Palchamy, A.; Sadasivam, S.; Sarkarung, S.; Wade, L.J.; Nguyen, Henry T. (Wiley, 2003)
Drought stress is the major constraint to rice (Oryza sativa L.) production and yield stability in rainfed ecosystems. Identifying genomic regions contributing to drought resistance will help develop rice cultivars suitable for rainfed regions through molecular marker assisted breeding. Quantitative trait loci (QTLs) linked to plant water stress indicators, phenology and production traits under irrigated and drought stress conditions were mapped by means of a doubled‐haploid (DH) population of 154 rice lines from the cross CT9993‐5‐10‐1‐M/IR62266‐42‐6‐2. The DH lines were subjected to water stress before anthesis in three field experiments at two locations. The DH lines showed significant variation for plant water stress indicators, phenology, plant biomass, yield and yield components under irrigated control and water stress. A total of 47 QTLs were identified for various plant water stress indicators, phenology, and production traits under control and water stress conditions in the field, which individually explained 5 to 59% of the phenotype variation. A region was identified on chromosome 4 that harbored major QTLs for plant height, grain yield, and number of grains per panicle under drought stress. By comparing the coincidence of QTLs with specific traits, we also genetically dissected the nature of association of root traits and capacity for osmotic adjustment with rice production under drought. Root traits had positive correlations with yield and yield components under drought stress. This study demonstrated that the region RG939‐RG476‐RG214 on chromosome 4 identified for root‐related drought resistance component QTLs also had pleiotropic effects on yield traits under stress. Consistent QTLs for drought resistance traits and yield under stress were detected and might be useful for marker‐assisted selection for rainfed rice improvement.